Medicolegal Autopsy Artefacts - Özer, Erdal; Şam, Bülent; Tokdemir, Murat Bülent; Yıldırım, Ali; Çetin, Gürsel (The Bulletin of Legal Medicine, 2010)
Crime scene investigation and performing autopsy is a process that requires expertise and experience. Autopsy doesn’t means only opening up three spaces as stated in the law. Autopsy is interpretation of findings detected by visual and microscopic examination. How to interpret the findings in the death which is deemed to occur after the postmortem formations which may overlap with antemortem findings that mislead us should be known. Forensic medical artifacts occur after death and misiterpere-ted as an important evidence of antemortem findings that are not related to previous diseases signs or changes and natural conditions of tissues. If forensic-medical artifacts are not well-defined and interpreted this can cause false manifestations of justice in terms of forensic medicine and autopsy practice. Key words: Autopsy, medicolegal artefact, postmortem changes